2012
DOI: 10.1186/1755-8794-5-15
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblasts from phenotypically normal palmar fascia exhibit molecular profiles highly similar to fibroblasts from active disease in Dupuytren's Contracture

Abstract: BackgroundDupuytren's contracture (DC) is a fibroproliferative disorder characterized by the progressive development of a scar-like collagen-rich cord that affects the palmar fascia of the hand and leads to digital flexion contractures. DC is most commonly treated by surgical resection of the diseased tissue, but has a high reported recurrence rate ranging from 27% to 80%. We sought to determine if the transcriptomic profiles of fibroblasts derived from DC-affected palmar fascia, adjacent phenotypically normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…The cellular and molecular physiology underlying this trend to recurrence remains under investigation. Our work has shown that not only fibroblasts from actively diseased cords, but also fibroblasts from phenotypically normal adjacent palmar fascia in DD have significantly altered patterns of gene expression compared to control cells from CT patients [37]. These nearby cells may therefore represent a residual manifestation of proto-disease after surgery, which may be stimulated by cytokine mediators to progress to active, frank recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The cellular and molecular physiology underlying this trend to recurrence remains under investigation. Our work has shown that not only fibroblasts from actively diseased cords, but also fibroblasts from phenotypically normal adjacent palmar fascia in DD have significantly altered patterns of gene expression compared to control cells from CT patients [37]. These nearby cells may therefore represent a residual manifestation of proto-disease after surgery, which may be stimulated by cytokine mediators to progress to active, frank recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, LiCl led to increased TOPFlash activity in nonpalmar fibroblasts from Dupuytren's patients and palmar dermal fibroblasts from individuals unaffected with Dupuytren's disease. It has previously been shown that fibroblasts from different sources may show divergent responses to the same stimuli (43), and more recently (29), it was reported that Dupuytren's myofibroblasts and fibroblasts from uninvolved palmar fascia from the same patients both expressed genes related to Wnt/β-catenin pathway, unlike fascial-derived fibroblasts from individuals without Dupuytren's disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, this approach has limitations. The palmar fascia over the carpal tunnel is rarely affected by Dupuytren's disease in susceptible individuals, and the transverse carpal ligament is always unaffected; hence, it is possible that the constituent cells are inherently different (29). Furthermore, with the exception of nodules in Dupuytren's disease, fascia is sparsely populated by cells and hence to obtain adequate numbers, most authors use cells to passage 5 (12).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of collagenases and their inhibitors in the normal ligament differs from that seen in the palmar fascia and nodule ligaments from Dupuytren's disease. The synthesis of MMPs and TIMP 1 is increased, despite the down‐regulation of TIMP3 and 4 in the mRNA profile in the myofibroblasts from Dupuytren's patients, as compared to normal ligament …”
mentioning
confidence: 93%